2020
DOI: 10.11002/kjfp.2020.27.4.487
|View full text |Cite
|
Sign up to set email alerts
|

Quality and antioxidant properties of wheat cookies supplemented with pak choi powder

Abstract: The replacing effect of pak choi powder (PCP) on the quality characteristics and antioxidant activities of wheat cookies was investigated in order to develop functionally and nutritionally improved food. The incorporation of PCP to wheat flour significantly affected the physicochemical properties of the cookie dough and cookies. Increased levels of incorporation remarkably increased the density of the cookie dough and the hardness of the cookies but decreased the cookie spread and loss rate. The L* and b* colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Thie increase could be related to the significant amounts of polyphenols present in MBP (Girones-Vilaplana et al, 2012;Romero-Gonzalez et al, 2020). Cookies supplemented with powders of cranberry (Choi and Lee, 2015), flaxseed (Kaur et al, 2017), pak choi (Lee, 2020b), and wheat-hog plum bagasse (Oladunjoye et al, 2021) have shown a similar increase in the antioxidant activity.…”
Section: Radical Scavenging Activitiesmentioning
confidence: 97%
See 1 more Smart Citation
“…Thie increase could be related to the significant amounts of polyphenols present in MBP (Girones-Vilaplana et al, 2012;Romero-Gonzalez et al, 2020). Cookies supplemented with powders of cranberry (Choi and Lee, 2015), flaxseed (Kaur et al, 2017), pak choi (Lee, 2020b), and wheat-hog plum bagasse (Oladunjoye et al, 2021) have shown a similar increase in the antioxidant activity.…”
Section: Radical Scavenging Activitiesmentioning
confidence: 97%
“…Table 2 presents the physicochemical characteristics of cookies supplemented with different levels of MBP. The spread of cookies is an indicator of how the dough is pushed outward during the baking process, resulting in reduced thickness and increased diameter (Lee, 2020b). The spread factor has been widely used as a cookie quality indicator, and spread of cookies is a relatively complex phenomenon influenced by various factors (Pareyt et al, 2009), including the type and absorption of flour, the type and addition of fat and sugar, the kneading time and method, and baking time and temperature (Koh and Noh, 1997).…”
Section: Physicochemical Characteristics Of Cookiesmentioning
confidence: 99%
“…35 While for the supplemented cookies, the phenolic content can be attributed to gallic acid, gentisic acid, epicatechin, p-coumaric acid, vanillic acid, and chlorogenic acids, as evidenced by research. 36 The TFC of supplemented cookies can be attributed to ferulic acid, catechin, and 90 different flavonoids in the BG peel, including isoflavones, pcoumaric acid, dihydroflavones, chalcones, and carbonosides. 37 Analysis of the Antioxidant Potential of BG Powder.…”
Section: Analysis Of Phenols and Flavonoidsmentioning
confidence: 99%